Hadis tentang Toleransi dalam Hutang Piutang Guna mewujudkan Perdamaian di Indonesia - Syifa Salsabila (Gunung Djati Conference Series, 2023)
This study aims to discuss the hadith about religious tolerance. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about tolerance for debts in the history of Ibn Majah No. 2411. The results and discussion of this study indicate that the status of hadith is of authentic quality which meets the accepted qualifications for Islamic propositions and practice. This study concludes that the hadith narrated by Ibn Majah No. 2411 is relevant as an argument and motivation for developing tolerance in debt problems in Indonesia.